Guillain‐Barré Syndrome in the First Trimester of Pregnancy and its Improvement by Rehabilitation. Issue 1 (27th June 2014) - Wada, Mikio; Ueda, Hiromi; Watanabe, Akiko; Yuki, Natsuko; Yamashita, Sadao
Abstract : A 31‐year‐old healthy mother of twins developed Guillain‐Barré syndrome in her fourth gestational week of pregnancy. Impaired motor coordination, sensation, and joint position sense were observed. Immunoglobulin therapy was not performed given the early stage of pregnancy. She received rehabilitation to accommodate changes in her body shape and movements necessary for pregnancy, childbirth, and childcare. The patient delivered a healthy baby by cesarean section. By 42 weeks postpartum, she was capable of almost all housework activities and childcare. Family support was important in this case. Patient‐oriented intervention, which included periodic confirmation and establishment of goals in each phase and continuity of intervention, was also essential.